Synaptic physiology of horizontal connections in the cat's visual cortex - Hirsch, JA (J Neurosci, 1991)
Horizontal connections are a principal component of intrinsic cortical circuitry. They arise mainly from pyramidal cells and course parallel to the brain's surface for distances as long as 8 mm, linking columns with shared orientation preference and allowing cells to integrate visual information from outside their receptive fields. We examined the synaptic physiology of the horizontal pathway in slices of the cat's striate cortex and found that activating lateral fibers produced both excitation and inhibition. We recorded the postsynaptic responses of identified pyramidal cells in layer 2 + 3 of area 17 to electrical shocks applied at three sites: in the home column of the impaled neuron either in layer 2 + 3 or 4, or at a lateral distance of 0.9–3 mm in layer 2 + 3. Within the home column, suprathreshold stimuli produced compound EPSPs with action potentials, followed by fast, GABAAergic IPSPs and a slower, GABABergic IPSP. For the distant stimulating site, the threshold response was an EPSP. Stronger shocks frequently evoked a disynaptic, GABAAergic IPSP that truncated the EPSP and could dominate the postsynaptic response. At the resting potential, the horizontally evoked EPSP was too small to elicit spikes. With depolarization of the membrane, however, it grew several hundred-fold. This amplification was blocked by N-(2,6-dimethylphenylcarbamoylmethyl)triethylammonium bromide (QX-314), but not by 2-amino-5-phosphonovalerate (APV), indicating that it was mediated by Na+ channels, rather than by NMDA receptors. We propose that the horizontal connections provide the means for stimuli outside the receptive field to modulate activity elicited within its confines. The voltage-dependent enhancement of the laterally evoked EPSP may explain why stimulating the surround by itself fails to drive cells but can facilitate their response to stimuli within the receptive field. The ability to initiate disynaptic inhibition from lateral sites shows that recruiting appropriate groups of horizontal fibers can also have a suppressive effect. Thus, the effect of horizontal input is state dependent, with the size and sign of the laterally evoked response changing according to the balance of converging inputs.